Analiza semiologiczna współczesnego słuchowiska - Bachura, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
Except an interpretative aspect of the psychological and social radio-play, deliberations on unvisual signs meaning were a subject of this article. The aim of my semiotic analysis was an attempt to indicate on a lot of possibilities of sound matter. A place of modern radio-play among texts of 21st century culture is also important.